Combined Treatments of Underground Coal Slurry: Laboratory Testing and Field Application - Xinguo Zhang (MDPI AG, 2021)
During the coal mining process, underground water is generated from the longwall face. In the meantime, the coal cutting process would produce coal particles. Coal slurry is generated in the underground working site, especially for water abundant coal mines. The generated coal slurry is treated to prevent water pollution. Due to the extensively existing of the suspended solid, the traditional process method would often introduce new problems. In this study, laboratory testing was conducted to investigate the characteristics, including the particle size distribution of the coal sludge, coal slurry compositions, slurry viscosity and coal mine water quality. In order to improve the coal slurry treatment efficiency, based on the laboratory results, a novel combined treatment of underground coal slurry is proposed. First, the coarse grained coal slurry is process by a vibrating screening machine. Then, the coal slurry containing fine coal powders is processed through a settling pond. The sedimentation results of the coal solid materials are analyzed. The polymer flocculant is also added into the coal slurry to improve the sedimentation. These combined treats of the coal slurry significantly remove the suspended solid and improve the quality of the coal mine water. Based on the laboratory testing, the specific details of the field applications are designed. The key novelty of this paper is the underground background. All of these treatments are based on the underground environment and are capable of being applied in underground workings. From field applications and observations, these novel combined treatments of coal slurry in the underground site are effective. This study provides a novel method to treat the coal slurry, which has innovations from engineering aspect. These procedures are useful for the underground coal slurry treatment, especially for water-abundant coal mines. The normal coal production is guaranteed and less affected by the coal slurry discharge process. Meanwhile, the water pollution problem is much addressed and the damage of coal slurry to the environment is reduced.